2019
DOI: 10.7759/cureus.4827
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety Profile of Lofexidine Hydrochloride in Treating Opioid Withdrawal Symptoms: A Review of Literature

Abstract: Opioid use disorder (OUD) is a rapidly growing challenge worldwide and is characterized by an increase in dependence on opioids up to a point that a person loses control over the drug use. Multiple drugs are approved for its treatment, including methadone, buprenorphine, and diazepam. Although not approved, clonidine is also used for the treatment of OUD. On May 16, 2018, the United States Food and Drug Administration (FDA) approved a new drug lofexidine hydrochloride for the treatment of opioid withdrawal sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Opioid-free treatments have been used in clinical settings to control withdrawal symptoms in abstaining patients [6]. Alpha-adrenergic agonists, such as lofexidine [67], clonidine or tizanidine [68], have been shown to be superior to placebo control to decrease anxiety and autonomic hyperactivity, but not as effective as opioid-based treatments in maintaining abstinence. Such agents are also used prudently as they might produce hypotension in these patients [24,68,6].…”
Section: Potential Non-opioid Treatments For Oudmentioning
confidence: 99%
“…Opioid-free treatments have been used in clinical settings to control withdrawal symptoms in abstaining patients [6]. Alpha-adrenergic agonists, such as lofexidine [67], clonidine or tizanidine [68], have been shown to be superior to placebo control to decrease anxiety and autonomic hyperactivity, but not as effective as opioid-based treatments in maintaining abstinence. Such agents are also used prudently as they might produce hypotension in these patients [24,68,6].…”
Section: Potential Non-opioid Treatments For Oudmentioning
confidence: 99%
“…The sympatholytic α-2 agonists lofexidine and clonidine have been implicated as potential alternatives or adjuncts to long-acting opioids. 6,7 Although this connection has led to considerations in the pharmacology of opioid withdrawal, to our knowledge, it has rarely been discussed in the context of cardiac complications such as TCM.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent relapse by reducing the intensity and duration of opioid withdrawal symptoms, a variety of different medications are used, including alpha-2 adrenergic agonists (clonidine or lofexidine), and adjuvant agents that help mitigate individual symptoms of opioid withdrawal such as non-steroidal anti-inflammatory agents (NSAIDs) against pain (e.g., ibuprofen), antihistamines (e.g., hydroxyzine), anti-emetics against nausea (e.g., ondansetron), and anti-diarrheal drugs (e.g., loperamide). Double-blind, placebo-controlled randomized trials in humans have shown that both clonidine and lofexidine are effective in mitigating opioid withdrawal symptoms (Rehman et al 2019 ; Alam et al 2020 ). However, a high incidence of adverse effects is commonly reported for both treatments, including sedation, dry mouth, hypotension, drowsiness, and dizziness (Gowing et al 2014 ; Hussain et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%